Preparation method and application of (NH4) AZ3 type ternary metal halide single crystal nanosheet
The preparation of layered (NH4) AZ3 type ternary metal halide single crystal material through chemical vapor phase transport method, solving the problem of inhibition of transport performance and lattice distortion in optoelectronic devices, and achieving high quality Preparation of 2D single crystal nanosheets and excellent photoelectric properties.
Patent Information
- Application Number
- CN202411431599.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing 2D perovskite materials have problems with inhibition of transport performance and lattice distortion in optoelectronic devices, mainly due to the introduction of long-chain amine organic ligands.
The chemical vapor phase transport method is used to prepare layered (NH4) AZ3 type ternary metal halide single crystal material. By controlling the reactant composition and temperature gradient, the introduction of long-chain amine organic ligands will be avoided, and directly through mechanical peeling or solution intercalation. Single crystal nanosheets were obtained by peeling.
It realizes that high-quality 2D single-crystal nanosheets can be obtained without surface passivation, reduces the scattering of defects on carriers, improves the photoelectric performance of the material, and is suitable for optoelectronic devices such as light emitting diodes and photodetectors.
Smart Images

Figure CN119465386A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal halide perovskite materials, and in particular to a preparation method and application of a (NH4)AZ3 type ternary metal halide single crystal nanosheet. Background Art
[0002] Ternary metal halide perovskites have broad application prospects in the fields of solar cells, light-emitting diodes, photodetectors, etc. due to their high carrier mobility and high light absorption coefficient. Compared with three-dimensional (3D) metal halide perovskites, 2D metal halide perovskite materials with quantum confinement effect have shown greater advantages in the field of optoelectronic devices due to their stronger stability, higher photosensitivity, thickness-dependent band gap and other characteristics. However, 2D perovskite materials are usually introduced into 3D perovskite structures by long-chain amine organic ligands, and the 3D structure is cut along a certain direction to form a sheet structure. Although the passivation effect of long-chain amine organic ligands on surface dangling bonds and defects greatly improves the stability of 2D perovskite materials, the long-chain amine organic ligand cations in the obtained 2D perovskite materials always have a strong interaction between H and halogen, which is easy to inhibit the transport performance of the material as an optoelectronic material, and in the preparation process, due to the lattice mismatch between organic amines and perovskites, it is easy to cause large lattice distortion.
[0003] Layered structural materials refer to a new type of material that is bonded by strong covalent or ionic bonds within the layers and stacked together by weak van der Waals forces. It is easy to obtain the corresponding 2D nanosheets by peeling. Chemical vapor transport is a method for growing high-quality single crystal materials. Generally, the material is volatilized and chemically reacted under heating and other conditions, and then transported to a lower temperature location for crystallization and growth of single crystal materials. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing (NH4)AZ3 type ternary metal halide single crystal nanosheets and its application. The method is easy to control and adopts chemical vapor transport method to obtain different layered single crystals by controlling the reactant composition, the temperature and temperature difference between the reaction end and the growth end, and controlling the peeling conditions to obtain single crystal nanosheets with different numbers of layers.
[0005] The technical solution of the present invention is:
[0006] A method for preparing (NH4)AZ3 type ternary metal halide single crystal nanosheets, firstly using the "chemical vapor transport" method, with metal Bi or Sb and NH4I or NH4Br as precursors, elemental iodine or bromine as a transport agent, to prepare layered (NH4)AZ3 ternary halide single crystal materials, and then obtaining single crystal nanosheets by mechanical exfoliation or solution intercalation exfoliation. This method obtains different layered (NH4)AZ3 type ternary halide materials by regulating the type of precursor salt, the temperature and temperature difference between the reaction end and the growth end, and controls the exfoliation conditions to obtain single crystal nanosheets with different numbers of layers.
[0007] The method for preparing (NH4)AZ3 type ternary metal halide single crystal nanosheets adopts the "chemical vapor transport" method to prepare layered (NH4)AZ3 type ternary halide single crystal materials. The specific process is as follows: first, the reactants obtained by mixing metal Bi or Sb, halide salt NH4I or NH4Br and elemental iodine or bromine are sealed in a quartz reactor; then the quartz reactor is placed in a tubular furnace, and the temperatures at both ends of the quartz reactor are controlled so that the reactants volatilize, decompose and react chemically at the high-temperature reaction end, and then deposit and grow layered (NH4)AZ3 type ternary halide single crystal materials at the low-temperature growth end; finally, the elemental iodine or bromine is removed by vacuum heating.
[0008] The preparation method of the (NH4)AZ3 type ternary metal halide single crystal nanosheets, in the process of preparing layered (NH4)AZ3 type ternary halide single crystal material by chemical vapor transport method, the content of metal Bi or Sb in the reactant is 20wt%~38.6wt%, the content of NH4I and NH4Br in the reactant is 40wt%~51.2wt%, and the content of transport agent elemental iodine or bromine in the reactant is 10.2wt%~40wt%.
[0009] The method for preparing (NH4)AZ3 type ternary metal halide single crystal nanosheets, in the process of preparing layered (NH4)AZ3 type ternary halide single crystal material by chemical vapor transport method, controls the temperature of the high temperature reaction end of the quartz reactor to 450℃~750℃, the temperature of the low temperature growth end to 200℃~450℃, the temperature gradient between the high temperature reaction end and the low temperature growth end to be 25~30℃ / cm, and the reaction time is 72h~168h.
[0010] The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheets removes the transport agent elemental iodine or bromine by vacuum annealing at a temperature of 60°C to 90°C for 12h to 24h.
[0011] The method for preparing (NH4)AZ3 type ternary metal halide single crystal nanosheets adopts mechanical exfoliation or solution intercalation exfoliation to obtain (NH4)AZ3 type ternary metal halide single crystal nanosheets with different numbers of layers; wherein the mechanical exfoliation method is to use Scotch tape or blue film tape to repeatedly thin the ternary halide single crystal material; the process of preparing single crystal nanosheets by solution intercalation exfoliation method is as follows: placing the prepared layered (NH4)AZ3 type ternary halide single crystal material in N-methylpyrrolidone solution for ultrasonic exfoliation; or in a reactor containing 0.5mmol / L to 2mmol / L n-butyllithium hexane solution, intercalating the single crystal material, and then ultrasonically exfoliating in solvent ethanol, isopropanol or formamide.
[0012] The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheets has a layer number of 1 to 100 layers, a thickness of 0.75nm to 75nm, and a band gap of 3.5eV to 1.4eV.
[0013] The application of the (NH4)AZ3 type ternary metal halide single crystal nanosheets and the method to obtain the (NH4)AZ3 type ternary metal halide single crystal nanosheets have thickness-dependent band gaps, high crystal quality and excellent photoelectric properties, and are widely used in the field of photoelectric devices such as light-emitting diodes or photodetectors.
[0014] The design concept of the present invention is:
[0015] The present invention adopts the method of "chemical vapor transport-stripping" to prepare a new type of (NH4)AZ3 type ternary metal halide single crystal nanosheet. First, the chemical vapor transport method is adopted, with metal Bi, Sb and NH4I, NH4Br as precursors, and elemental iodine or Br as a transport agent, to prepare a layered (NH4)AZ3 type ternary metal halide single crystal material. Elemental iodine or Br is heated and sublimated at the high-temperature reaction end as a transport agent, and it can directly react with metal Bi or Sb to generate corresponding trihalides BiI3, SbI3, BiBr3, SbBr3. And these metal halides as core reactants can also further react with volatile NH4I, NH4Br or their decomposition products, and finally transported to the low-temperature growth end to crystallize and grow layered (NH4)AZ3 type ternary halide single crystals. In the (NH4)AZ3 type ternary metal halide, A represents Bi or Sb, and Z represents I or Br. This method is easy to control. By adjusting the reactant components and composition and controlling the reaction temperature and temperature difference, different layered (NH4)AZ3-type ternary metal halide single crystal materials can be prepared. Since the obtained ternary halide material sheets have no surface dangling bonds, the layers are connected by weak van der Waals forces, and it is easy to obtain the corresponding 2D single crystal nanosheets by peeling, so there is no need to introduce long-chain amine organic ligands to passivate their surfaces. At the same time, since the single crystal materials prepared by chemical vapor transport method are of high quality and few defects, the scattering of defects on carriers can be reduced, greatly reducing non-radiative recombination losses. In addition, the quantum confinement effect makes the band gap and optoelectronic properties of single crystal nanosheets have a layer number dependence. Therefore, the obtained 2D single crystal nanosheets have excellent optoelectronic properties and are expected to be widely used in optoelectronic devices.
[0016] The advantages and beneficial effects of the present invention are:
[0017] 1. The present invention proposes to use trihalides BiI3, SbI3, BiBr3, and SbBr3 with layered structures as core reactants, and develop a chemical vapor transport method to prepare layered (NH4)AZ3-type ternary halide single crystal materials. Single crystal nanosheets can be obtained by simple peeling without surface passivation, which solves the problem that the introduction of long-chain organic ligands will inhibit the transport performance of 2D ternary metal halide materials and cause lattice distortion.
[0018] 2. The (NH4)AZ3 type ternary metal halide single crystal nanosheets obtained by the present invention have a thickness-dependent band gap, high crystal quality and excellent photoelectric properties, and can be widely used in photoelectric devices such as light-emitting diodes and photodetectors. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a flow chart of the "chemical vapor transport-stripping" method for preparing layered (NH4)AZ3 type ternary metal halide single crystal material.
[0020] Figure 2 Macroscopic photograph (left) and microscopic transmission electron microscope photograph (right) of the (NH4)BiI3 single crystal prepared by the "chemical vapor transport method" in Example 1.
[0021] Figure 3 This is a scanning photograph of 10 to 15 layers of (NH4)BiI3 single crystal nanosheets obtained by mechanical exfoliation using Scotch tape in Example 1. DETAILED DESCRIPTION
[0022] In the specific implementation process, the present invention utilizes the "chemical vapor transport" method, with metal Bi, Sb and NH4I, NH4Br as precursors, elemental iodine or Br as transport agents, and controls the reactant composition, the temperature and temperature difference between the reaction end and the growth end to prepare a (NH4)AZ3 type ternary metal halide single crystal material with a layered structure, and obtains a 2D single crystal (NH4)AZ3 single crystal nanosheet by mechanical exfoliation or solution intercalation exfoliation.
[0023] like Figure 1As shown, the present invention first prepares a layered (NH4)AZ3 type ternary metal halide single crystal material by a "chemical vapor transport" method. The reactant metal Bi or Sb and the halide salt NH4I or NH4Br, and the transport agent elemental iodine or bromine are mixed and sealed in a quartz reactor, wherein the content of the metal Bi or Sb is 20wt% to 38.6wt%, the content of the halide salt NH4I or NH4Br is 40wt% to 51.2wt%, and the content of the transport agent elemental iodine or bromine is 10.2wt% to 40wt%; then, the quartz reactor is placed in a tubular furnace, so that the reactants are volatilized, decomposed and chemically reacted at the high temperature reaction end. The quartz reactor is subjected to a reaction to deposit and grow a layered (NH4)AZ3-type ternary metal halide single crystal material at the low-temperature growth end. The high-temperature reaction end temperature of the quartz reactor is 450°C to 750°C, the low-temperature growth end temperature is 200°C to 450°C, the temperature gradient between the high-temperature reaction end and the low-temperature growth end is 25 to 30°C / cm, and the reaction time is 72h to 168h. After cooling to room temperature, the sample is taken out and the elemental iodine or bromine is removed by vacuum annealing at a temperature of 60°C to 90°C for 12h to 24h. Finally, the obtained layered (NH4)AZ3-type ternary metal halide single crystal material is mechanically exfoliated using Scotch tape (produced by 3M Company, USA) or blue film tape; or ultrasonic exfoliation is performed in N-methylpyrrolidone (NMP) solution; or the layered single crystal is intercalated in a reactor containing 0.5mmol / L to 2mmol / L n-butyllithium hexane solution, and ultrasonic exfoliation is performed in solvents such as ethanol, isopropanol or formamide to obtain 1 to 100 layers of (NH4)AZ3-type ternary metal halide single crystal nanosheets with a thickness of 0.75nm to 75nm, and a band gap of 3.5eV to 1.4eV.
[0024] In order to make the technical solutions and advantages of the present invention more clear, a detailed description will be given below in conjunction with specific embodiments.
[0025] Embodiment 1:
[0026] In this embodiment, metal Bi, halide salt precursor NH4I and transport agent elemental iodine are first mixed and sealed in a quartz reactor; wherein the content of metal Bi is 35.5wt%, the content of NH4I is 40wt%, and the content of elemental iodine is 24.5wt%. Then, the quartz reactor is placed in a tubular furnace, and the temperature of the high-temperature reaction end of the quartz reactor is controlled to be 500°C, and the temperature of the low-temperature growth end is controlled to be 300°C. The temperature gradient between the high-temperature reaction end and the low-temperature growth end is 25°C / cm, so that metal Bi and I2 are sublimated and reacted at the high-temperature reaction end to generate BiI3, which further reacts with NH4I or its decomposition product and grows into (NH4)BiI3 at the low-temperature growth end. After reacting for 100 hours, cool to room temperature and take out the sample. After vacuum annealing at 60°C for 12 hours, a layered (NH4)BiI3 single crystal material ( Figure 2 Finally, 10 to 15 layers of (NH4)BiI3 single crystal nanosheets were obtained by mechanical exfoliation using Scotch tape ( Figure 3 ), with a thickness of 7.5 to 11.25 nm and a band gap of ~2.0 eV.
[0027] The obtained (NH4)BiI3 single crystal nanosheets were transferred to SiO2 / Si substrate with electrodes to prepare a transistor-type photodetector with a detection rate of 10 4 A / W.
[0028] Embodiment 2:
[0029] The difference from Example 1 is that the temperature of the high temperature reaction end of the quartz reactor is controlled to be 450°C, the temperature of the low temperature growth end is controlled to be 300°C, the temperature gradient between the high temperature reaction end and the low temperature growth end is 28°C / cm, and the reaction time is 72h. Finally, intercalation is carried out in a reactor of 2mmol / L n-butyl lithium hexane solution, and then ultrasonic exfoliation is carried out in an isopropanol solution to obtain a 5-10 layer single crystal nanosheet dispersion with a thickness of 3.75nm-8.25nm and a band gap of ~3.0eV.
[0030] The obtained (NH4)BiI3 single crystal nanosheet dispersion was formed into a film as a light-emitting layer by spin coating, and a blue light-emitting diode with a structure of ITO / PEDOT:PSS / PVK / (NH4)BiI3 / TPBi / LiF / Al was prepared, and its external quantum efficiency was 1.25%.
[0031] Embodiment 3:
[0032] The difference from Example 1 is that the metal used is Sb, and in the mixture of metal Sb, NH4I and elemental iodine: the content of metal Sb is 32wt%, the content of NH4I is 45wt%, and the content of iodine transport agent is 23wt%. The temperature of the high temperature reaction end of the quartz reactor is controlled to be 600℃, the temperature of the low temperature growth end is 300℃, the temperature gradient between the high temperature reaction end and the low temperature growth end is 26℃ / cm, the reaction time is 150h, and finally a large single crystal is obtained by vacuum heating annealing at 60℃ for 12h. Finally, 10 to 15 layers of (NH4)SbI3 single crystal nanosheets are obtained by mechanical stripping with blue film tape, with a thickness of 7.5 to 11.25nm and a band gap of 3.1eV.
[0033] The obtained (NH4)SbI3 single crystal nanosheets were transferred to SiO2 / Si substrate with electrodes to prepare a transistor-type photodetector with a detection rate of 10 3 A / W.
[0034] Embodiment 4:
[0035] The difference from Example 3 is that the temperature of the high temperature reaction end of the quartz reactor is controlled to be 450°C, the temperature of the low temperature growth end is controlled to be 250°C, the temperature gradient between the high temperature reaction end and the low temperature growth end is 25°C / cm, and the reaction time is 72h. Finally, after intercalation with 2mmol / L n-butyllithium solution, 5 to 10 layers of (NH4)SbI3 single crystal nanosheet dispersion are obtained by exfoliation in formamide solution, with a thickness of 3.75 to 8.25nm and a band gap of 3.65eV.
[0036] The obtained (NH4)SbI3 single crystal nanosheet dispersion was used to prepare a light-emitting layer by spin coating, and a blue light-emitting diode with a structure of ITO / PEDOT:PSS / PVK / (NH4)SbI3 / TPBi / LiF / Al was prepared, and its external quantum efficiency was 0.3%.
[0037] Embodiment 5:
[0038] The difference from Example 4 is that after intercalation with 0.5 mmol / L n-butyl lithium hexane solution, ultrasonic exfoliation in ethanol is performed to obtain a 50-60 layer single crystal nanosheet dispersion with a thickness of ∼37.5 nm and a band gap of ∼2.5 eV.
[0039] The obtained (NH4)SbI3 single crystal nanosheet dispersion was used to prepare a light-emitting layer by spin coating, and a green light-emitting diode with a structure of ITO / PEDOT:PSS / PVK / (NH4)SbI3 / TPBi / LiF / Al was prepared, and its external quantum efficiency was 1.5%.
[0040] Embodiment 6:
[0041] The difference from Example 1 is that the driving salt used is NH4Br, the content of NH4Br is 40wt%, the transport agent is bromine, the content is 24.5%, and the rest is metal Bi. The temperature of the high temperature reaction end of the quartz reactor is controlled to be 650℃, the temperature of the low temperature growth end is 200℃, and the temperature gradient between the high temperature reaction end and the low temperature growth end is 30℃ / cm. The metal Bi and Br2 are sublimated and reacted at the high temperature reaction end to generate BiBr3, which further reacts with NH4Br to generate layered (NH4)BiBr3, the reaction time is 160h, and then cooled to room temperature to take out the sample. After vacuum annealing at 80℃ for 18h, a layered (NH4)BiBr3 single crystal material is obtained. Finally, ultrasonic peeling is performed in NMP solution to obtain 5 to 10 layers of single crystal nanosheets with a thickness of 3.75nm to 8.25nm and a band gap of ~3.25eV.
[0042] The obtained (NH4)BiBr3 single crystal nanosheets were transferred to SiO2 / Si substrate with electrodes to prepare a transistor-type photodetector with a detection rate of 10 4 A / W.
[0043] Embodiment 7:
[0044] The difference from Example 1 is that the driving salt used is NH4Br, the content of NH4Br is 45wt%, the transport agent is bromine, the content is 34.5wt%, and the rest is metal Sb. The temperature of the high temperature reaction end of the quartz reactor is controlled to be 750℃, the temperature of the low temperature growth end is 300℃, and the temperature gradient between the high temperature reaction end and the low temperature growth end is 30℃ / cm. The metal Sb and Br2 are sublimated and reacted at the high temperature reaction end to generate SbBr3, which further reacts with NH4Br to generate layered (NH4)SbBr3, the reaction time is 160h, and then cooled to room temperature to take out the sample. After vacuum annealing at 80℃ for 20h, a layered (NH4)SbBr3 single crystal material is obtained. Finally, ultrasonic peeling is performed in an isopropanol solution to obtain 1 to 5 layers of single crystal nanosheets with a thickness of 1.25nm to 6.05nm and a band gap of ~3.5eV.
[0045] The obtained (NH4)SbBr3 single crystal nanosheets were transferred to SiO2 / Si substrate with electrodes to prepare a transistor-type ultraviolet photodetector with a detection rate of 10 4 A / W.
[0046] The results of the embodiments show that the present invention first grows a (NH4)AZ3 type ternary halide single crystal material having a layered structure by the method of "chemical vapor transport". Then, a (NH4)AZ3 type ternary metal halide single crystal nanosheet is obtained by mechanical exfoliation or solution intercalation exfoliation. The method is simple in process, and different layered (NH4)AZ3 type ternary metal halide single crystals are obtained by regulating the type of precursor salt, the temperature and temperature difference between the reaction end and the growth end, and the exfoliation conditions are controlled to obtain single crystal nanosheets with different numbers of layers. The obtained (NH4)AZ3 type ternary metal single crystal nanosheet has adjustable thickness and band gap, and has broad application potential in the field of optoelectronic devices such as light-emitting diodes and photodetectors.
Claims
1. A method for preparing (NH4)AZ3 type ternary metal halide single crystal nanosheets, characterized in that: First, the "chemical vapor transport" method is used to prepare layered (NH4)AZ3 ternary halide single crystal materials with metal Bi or Sb and NH4I or NH4Br as precursors and elemental iodine or bromine as transport agents, and then single crystal nanosheets are obtained by mechanical exfoliation or solution intercalation exfoliation. This method obtains different layered (NH4)AZ3 type ternary halide materials by regulating the type of precursor salt, the temperature and temperature difference between the reaction end and the growth end, and controls the exfoliation conditions to obtain single crystal nanosheets with different numbers of layers.
2. The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheet according to claim 1, characterized in that: The specific process of preparing layered (NH4)AZ3 type ternary halide single crystal material by the "chemical vapor transport" method is as follows: first, the reactants of metal Bi or Sb, halide salt NH4I or NH4Br and elemental iodine or bromine are sealed in a quartz reactor; then the quartz reactor is placed in a tube furnace, and the temperature at both ends of the quartz reactor is controlled to make the reactants volatilize, decompose and react chemically at the high-temperature reaction end, and then deposit and grow layered (NH4)AZ3 type ternary halide single crystal material at the low-temperature growth end; finally, the elemental iodine or bromine is removed by vacuum heating.
3. The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheet according to claim 2, characterized in that: In the process of preparing layered (NH4)AZ3 type ternary halide single crystal materials by chemical vapor transport, the content of metal Bi or Sb in the reactants is 20wt%~38.6wt%, the content of NH4I and NH4Br in the reactants is 40wt%~51.2wt%, and the content of transport agent elemental iodine or bromine in the reactants is 10.2wt%~40wt%.
4. The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheet according to claim 2, characterized in that: In the process of preparing layered (NH4)AZ3 type ternary halide single crystal materials by chemical vapor transport method, the temperature of the high temperature reaction end of the quartz reactor is controlled to be 450℃~750℃, the temperature of the low temperature growth end is 200℃~450℃, the temperature gradient between the high temperature reaction end and the low temperature growth end is 25~30℃ / cm, and the reaction time is 72h~168h.
5. The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheet according to claim 2, characterized in that: The transport agent elemental iodine or bromine is removed by vacuum annealing at a temperature of 60°C to 90°C for 12h to 24h.
6. The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheet according to claim 1, characterized in that: Mechanical exfoliation or solution intercalation exfoliation is used to obtain (NH4)AZ3 type ternary metal halide single crystal nanosheets with different number of layers; wherein, the mechanical exfoliation method is to use Scotch tape or blue film tape to repeatedly thin the ternary halide single crystal material; the process of preparing single crystal nanosheets by solution intercalation exfoliation method is: placing the prepared layered (NH4)AZ3 type ternary halide single crystal material in N-methylpyrrolidone solution for ultrasonic exfoliation; or in a reactor with a content of 0.5mmol / L to 2mmol / L n-butyllithium hexane solution, the single crystal material is intercalated, and then ultrasonically exfoliated in solvent ethanol, isopropanol or formamide.
7. The method for preparing the (NH4)AZ3 type ternary metal halide single crystal nanosheet according to claim 1, characterized in that: The obtained (NH4)AZ3 type ternary metal halide single crystal nanosheet has 1 to 100 layers, a thickness of 0.75nm to 75nm, and a band gap of 3.5eV to 1.4eV.
8. An application of (NH4)AZ3 type ternary metal halide single crystal nanosheets prepared by the method according to any one of claims 1 to 7, characterized in that: The (NH4)AZ3-type ternary metal halide single crystal nanosheets obtained by this method have thickness-dependent band gaps, high crystal quality and excellent photoelectric properties, and are widely used in the field of optoelectronic devices such as light-emitting diodes or photodetectors.
Citation Information
Patent Citations
Method for preparing two-dimensional inorganic nanomaterial by mechanical force intercalation stripping
CN109250693A
Method for preparing layered perovskite compound thin film with organic ammonium layers and inorganic layers
US20020124790A1
Organometal Halide Perovskite Nanoplatelets, Devices, and Methods
US20170084848A1
Ultrathin nanoribbons of highly anisotropic layered material and method of production
US20240059565A1